El Excentrico, 1960-11-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
November 05, 1960 [20 de noviembre de 1960]. Ano 11, No 2. Cover has a group photograph of people in formal attire advertising the Cuahtemoe formal dance, which took place on November 11 at the Hawaiian Gardens Terrace.